2019
DOI: 10.1182/blood-2019-127987
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib Induces Cardiotoxicity Via ß5/ß2-Specific Proteasome Subunit Inhibition Pattern

Abstract: BACKGROUND All proteasome inhibitors (PI) approved for Multiple Myeloma (MM) treatment, Bortezomib (BTZ), Ixazomib (IXA) and Carfilzomib (CFZ), by design target the rate-limiting ß5 proteolytic proteasome subunit, but differ in their co-inhibition of the ß1 or ß2 proteolytic subunits at higher doses. CFZ is unique in inducing ß5/ß2 co-inhibition in a dose-dependent manner, which results in increased proteotoxic stress and higher cytotoxicity compared to the ß5/ß1 co-inhibition pattern mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The last finding derived from in vivo experiments agrees with clinical observations pointing to a less cardiotoxic nature of BTZ compared with CFZ [ 395 , 396 ]. It is also in keeping with the results of comparative analysis of CFZ, BTZ, and ixazomib (IXA), which showed that the most explicit activity on cardiomyocytes of the former is associated with its β5/β2-specific proteasome subunit inhibition pattern [ 397 ].…”
Section: Introduction or A Few Words About Cardiooncologysupporting
confidence: 68%
“…The last finding derived from in vivo experiments agrees with clinical observations pointing to a less cardiotoxic nature of BTZ compared with CFZ [ 395 , 396 ]. It is also in keeping with the results of comparative analysis of CFZ, BTZ, and ixazomib (IXA), which showed that the most explicit activity on cardiomyocytes of the former is associated with its β5/β2-specific proteasome subunit inhibition pattern [ 397 ].…”
Section: Introduction or A Few Words About Cardiooncologysupporting
confidence: 68%
“…Different theories suggest that proteasome inhibition induces oxidative stress and leads to hypertension, vascular dysfunction and an increase in coronary vascular tone and reactivity. 16,17…”
Section: Discussionmentioning
confidence: 99%
“…The median OS of 4.75 years observed in our cohort including older and comorbid patients is remarkably well in line with OS reported from previous prospectively designed phase three studies with bortezomib-or lenalidomide-based treatment approaches. 5,[13][14][15][16][17] Both studies, the POLLUX and CASTOR included only very few patients above 75 years (<15% of the overall study population was ≥75 years). 11 In our real-world sample, almost half of the patients (41/96) patients were older than 75 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation